PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBANTU APLIKASI CANVA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SDN 14 PULAU PUNJUNG - Amin, Alhafizin Amin; Ningsih, Sri Yunimar; Darniyanti, Yulia (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This research was motivated by schools that had not used interactive media that could attract students' attention. The same thing was also found when conducting PLP, several problems were found, namely that teachers only used lecture and discussion learning methods and still had not used more interesting media which resulted in less than optimal student understanding and students feeling bored. Therefore, researchers are interested in developing Animated Video learning media. The type of research is development research, namely using the ADDIE development model consisting of the analysis stage, the analysis stage includes material analysis, analysis of student needs and student characteristics. The planning stage (design) the planning stage is the design of the animated video learning media, namely the instrument design and framework design. The development stage (develop) the development stage is a validation test. The implementation stage (implementation) the implementation stage is carried out for practicality and effectiveness. The evaluation stage (evaluation) is carried out at each stage starting from analysis, design, develop and implementation.The results of the validation assessment of Animation Videos in the validation test by 3 experts had an average score of language validation of 84.1%, media validation of 85.5% and material validation of 89.9% included in the very valid category, meaning that the application is in accordance with the language, media and learning materials. The practicality test of educators with an average score of 75% was categorized as very practical and from students 90.445% were categorized as very practical, meaning that the application can be used easily for the learning process, while the results of the effectiveness of learning animation videos with a score of 95% were categorized as very effective, meaning that animation videos can improve student learning outcomes.